Case Series of Brittle Cornea Syndrome - Taher Eleiwa; Mariam Raheem; Nimesh A. Patel; Audina M. Berrocal; Alana Grajewski; Mohamed Abou Shousha (Case Reports in Ophthalmological Medicine)
Purpose. This case series demonstrate diagnostic features, treatment options, and challenges for Brittle Cornea Syndrome. Observations. Three cases presented with bluish sclera and extremely thin cornea. Genetic workup was performed and confirmed the diagnosis of Brittle Cornea Syndrome, a rare autosomal recessive disorder characterized by corneal thinning and blue sclera. Case 1 was a 4-year-old boy who developed cataract and glaucoma after undergoing right tectonic penetrating keratoplasty (PK) secondary to a spontaneous corneal rupture. Glaucoma was controlled medically. Later, the kid underwent right transcorneal lensectomy and vitrectomy with synechiolysis. After 6 weeks, he sustained graft dehiscence that was repaired using onlay patch graft. Case 2 was a 7-year-old boy who underwent PK in the right eye, then a pericardial patch graft in the left eye following spontaneous corneal rupture. Glaucoma in both eyes was controlled medically. Case 3 was the 2-year-old sister of the 2nd case. She had a pachymetry of 238 μm OD and 254 μm OS. In the 3 cases, parents were instructed to take protective measures for both eyes and to continue with follow-up visits. Also, they were instructed to have regular screenings for late-onset hearing loss, dental abnormalities, and bone deformities. Conclusions. Long-term follow-up of children diagnosed with Brittle Cornea Syndrome is paramount to minimize the morbidity of corneal rupture and late-onset extraocular conditions.